Timing of Side-Dress Applications of Nitrogen for Corn in Conventional and No-Till Systems - D. W. Sweeney; D. E. Shoup (Kansas Agricultural Experiment Station Research Reports, 2017)
Corn yields were affected by tillage and nitrogen (N) side-dress options in 2016. Corn yields were 12% greater with conventional tillage than with no-till. Side-dress applications of N at V10 resulted in greater corn yield than side-dress N applications at V6.
Keywords: nitrogen; side-dress; corn; tillage; no-till